The statistical analysis of generalized adjacency and GA-clusters - Xu, Ximing (University of Ottawa (Canada), 2008)
In this thesis I study a parametrized definition of gene clusters that permits control over the trade-off between increasing gene content versus conserving gene order within a cluster. This is based on the notion of generalized adjacency, which is the property shared by any two genes no farther apart, in the linear order of a chromosome, than a fixed threshold parameter theta. We discuss the the statistical properties of generalized adjacency ( GA) and derive the limiting probability distribution of the number of GA for random genomes. We also propose a test for gene clusters satisfying the generalized adjacency criterion under the null hypothesis that the genes are ordered randomly along the genomes.
Keywords: Mathematics.; Statistics.